AAGBS series talk: i-Care: managing new norms - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
The AAGBS Series Talk, hosted by the Arshad Ayub Graduate Business School (UiTM), took place on 14 August 2020.The session, conducted via Google Meet, focused on "i-Care: Managing New Norms" featuring speaker Professor Dr. Nor’Azam Haji Mastuki (Dean AAGBS), Professor Dr. Rosmimah Mohd Roslin (Deputy Dean (Academic)), Assoc. Prof. Dr. Nor Hashima Hashim (Deputy Dean (Research, Consultancy, Publication & Student Development)) and Dr. Arlinah Abd. Rashid (Deputy Dean (Industry Linkages & Internationalization)).